Smart Gorden Menggunakan Arduino dan Telegram - Rian Sultan Asizan; Akmal Hidayah A; Muhammad Risal; Abdul Latief Arda (Ikatan Ahli Informatika Indonesia, 2023)
Curtains or curtains are a part of household appliances used to block light and visibility into the house, usually placed on windows and bedroom doors. However, we often forget to open and close windows when traveling, causing the air in the house to become damp and at night visibility can penetrate the glass, attracting thieves. Therefore, this research aims to create smart curtains that can open and close automatically and be controlled remotely via smartphones. This system implementation uses a real-time clock (RTC), button limit switches, and telegrams as inputs, Arduino Uno as processor, and LCD, telegrams, and stepper motors as outputs. With three control systems: manual with buttons, using RTC timer and using Telegram application. Research results show that smart curtain systems based on the Internet of Things (IoT) can work well when the average curtain opening and closing time is 32 seconds. To check timing accuracy based on timer input, there is no delay between input timing. and time on transient system Testing with Telegram input messages showed delivery latency with an average latency of 3.5 seconds.